As falhas paternas em Winnicott - Rosa, Claudia Dias (2011)
Devoted to Winnicottian psychoanalysis, this study has the following objectives: a) to analyze the father s contribution to the personal maturational process in its various stages; b) to explain possible paternal failures and how they are connected with the etiology of emotional disorders; c) to illustrate these failures and their consequences from early stages to that of triangular relationships. At the beginning of life, although the baby is not mature enough to establish a relationship with the father as a father, the paternal presence is fundamental to help the mother to be good enough or to make this task difficult to the mother. In the stage of concern, the child may be helped or not by the father in regard to the capacity of tolerating the conflict between love and hate. Finally, in the stage of triangular relationships, once the healthy child is already mature enough to establish, as a full person, direct relationships with the father (as a full person too), paternal contributions or failures influence directly the solution of the child s conflicts in regard to handling his/her instinctual drive s of genital order in his/her interpersonal relationships. Paternal failures were evaluated from the theoretical perspective and examined based on some clinical cases presented by Winnicott, according to maturational criteria which he suggested for the understanding of the etiology of emotional disorders